(untitled) (Politeja, 2019)
Russia attempts to revise a Western-led liberal world order. However, challenging the West seems to be a strategy aimed at improving Russia’s international standing. This strategy is undoubtedly ambiguous as Russia challenges the West, particularity the United States, and looks for a rapprochement at the same time. The Russian Federation abandoned the West in 2014 as a result of the annexation of the Crimean Peninsula what constituted breaking international law, andengagement into the war in the East Ukraine. Nevertheless, the milestone was not 2014, but 2008 when Russia had decided for the first time to use its military force against Georgia and indirectly against the growing Western military and political presence in this post-Soviet republic. This game changer was hardly a surprise, because several signals of a desire to challenge the Western-led world order had appeared in the past at least twice in president Putin’s speeches in 2007 at Munich Security Conference and in 2014 during Valdai Club session in Sochi. This article seeks to provide a take in the discussion about the way Russia has been trying to reshape the post-Cold War order. This paper probes the notion that Russia has become a revisionist state trying to shape a post-Western world order. Besides, there are a few questions to be answered, first of all whether anti-Westernism is in fact its goal or rather an instrument in regaining more effective impact on international politics and how it may influence the post-Cold War order despite its reduced political and economic potential.